2017
DOI: 10.1556/038.52.2017.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preventive and curative fungicide treatment on Fusarium proliferatum infected maize — a field trial

Abstract: There are extensive data on effects of antifungal agents on the plant pathogens, especially on Fusar iums spp. species. However, investigations on the interaction of chemicals and the treated cultivars are rare. The aim of the study was to test two types of fungicide mixtures, azoxystrobin-propiconazole, and prothioconazole-tebuconazole, which are applied in wheat cultivars intensively, on six fodder maize hybrids that were infected with Fusarium proliferatum in the R1 growth stage in a field trial. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Preventive application of trifloxystrobin + prothioconazole and azoxystrobin + cyproconazole + carbendazim (Figure 1a and 1b) showed low GER severity, corroborating the data found by Andriolli et al (1), who used the second fungicide mixture and rates. In their studies with Fusarium proliferatum infected maize, Pusztahelyi et al (20) concluded that the treatment with prothioconazole and tebuconazole was suitable when done before flowering, while azoxystrobin-propiconazole treatments were equally successful before and after maize flowering, considering the decreasing fumonisin concentration of kernels. Trifloxystrobin + prothioconazole (0.15 + 0.17 and 0.22 + 0.26 L ha -1 ), pyraclostrobin + metconazole (0.19 + 0.12 and 0.29 + 0.18 L ha -1 ) and carbendazim (1.0 L ha -1 ), applied at increasing rates, showed efficiency despite the preventive and/or curative spraying.…”
Section: Study Ii: Fungicide Ratesmentioning
confidence: 99%
“…Preventive application of trifloxystrobin + prothioconazole and azoxystrobin + cyproconazole + carbendazim (Figure 1a and 1b) showed low GER severity, corroborating the data found by Andriolli et al (1), who used the second fungicide mixture and rates. In their studies with Fusarium proliferatum infected maize, Pusztahelyi et al (20) concluded that the treatment with prothioconazole and tebuconazole was suitable when done before flowering, while azoxystrobin-propiconazole treatments were equally successful before and after maize flowering, considering the decreasing fumonisin concentration of kernels. Trifloxystrobin + prothioconazole (0.15 + 0.17 and 0.22 + 0.26 L ha -1 ), pyraclostrobin + metconazole (0.19 + 0.12 and 0.29 + 0.18 L ha -1 ) and carbendazim (1.0 L ha -1 ), applied at increasing rates, showed efficiency despite the preventive and/or curative spraying.…”
Section: Study Ii: Fungicide Ratesmentioning
confidence: 99%